Pengelolaan Administrasi Sekolah di RA Ar-Rafif Tirtomartani Sleman - Istiqomah, Atina (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
This study discusses how to manage an administrative school in RA Arrafif Tirtomartani Kalasan Sleman, the next method used in this study is a qualitative study describing how to manage an administration school in RA Arrafif Tirtomartani Kalasan Sleman. Data collection techniques used in this study are observation, interviews and documentation, then data analysis in this study uses miles and huberman data analysis using data reduction, data presentation and drawing conclusions. Based on data collection and analysis conducted on research findings on school administration management in RA Arrafif Tirtomartani Kalasan Sleman, while the results of this study include seven school administrations that manage well such as 1) school administration, 2) class administration, 3) student administration, 4) financial administration, 5) headmaster administration, 6) staffing administration, 7) administration of inventory, but there are some things that still lack.